2004
DOI: 10.1002/col.20063
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐regional comparison of colour emotions Part II: Qualitative analysis

Abstract: During the colour perception process, an associated feeling or emotion is induced in our brains

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 8 publications
3
50
0
Order By: Relevance
“…But this was not the case for warm -cool scale of colour emotion. Therefore, they extended their studies looking into the differences in lightness and chroma at 0 hue angle describing the differences between the three regions (Xin et al, 2004a;Xin, Cheng, Taylor, Sato & Hansuebsai, 2004b). Lee and Lee (2006) found that colour emotion was highly affected by its tone.…”
Section: Kaya and Eppsmentioning
confidence: 98%
See 1 more Smart Citation
“…But this was not the case for warm -cool scale of colour emotion. Therefore, they extended their studies looking into the differences in lightness and chroma at 0 hue angle describing the differences between the three regions (Xin et al, 2004a;Xin, Cheng, Taylor, Sato & Hansuebsai, 2004b). Lee and Lee (2006) found that colour emotion was highly affected by its tone.…”
Section: Kaya and Eppsmentioning
confidence: 98%
“…Therefore, this study is beneficial for designers to identify their ability and modality of changing, modifying or transforming a person's or society's emotion evoked by colour. Moreover, designers' understanding of target customers emotions and feelings would facilitate them to select the right colour for their products (Xin, Cheng, Taylor, Sato & Hansuebsai, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…The research indicated that the associations of colors of images to image words are based on the semantic axes e.g., cool -warm and soft -hard. Many researches [15,16] adopted this theory to build the relation between affective words and color themes. However, most of the previous studies have not taken into account the analysis of the topic of the images whose emotional expression are mainly focused, before showing the affective words and adjectives related to the impression of the images.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some researchers found that the influence of cultural background was very limited, whereas brightness and saturation were the most important factors influencing color emotion. For example, J. H. Xin et al investigated cross-regional color emotions, and found that the hue was much less predominant for color emotions than brightness and saturation [8].…”
Section: Introductionmentioning
confidence: 99%